Measurement of the Underlying Event Activity at the Lhc With ?s = 7 Tev and Comparison With ?s = 0:9 Tev - Demir, Durmuş Ali; Karapınar, Güler; Demir, Durmuş Ali; Karapınar, Güler (Springer Verlag, 2011)
A measurement of the underlying activity in events with a jet of transverse momentum in the several GeV region is performed in proton-proton collisions at √ s = 0:9 and 7TeV, using data collected by the CMS experiment at the LHC. The production of charged particles with pseudorapidity |η|<2 and transverse momentum pT >0:5 GeV/c is studied in the azimuthal region transverse to that of the leading set of charged particles forming a track-jet. A significant growth of the average multiplicity and scalar-pT sum of the particles in the transverse region is observed with increasing pT of the leading trackjet, followed by a much slower rise above a few GeV/c. For track-jet pT larger than a few GeV/c, the activity in the transverse region is approximately doubled with a centreof- mass energy increase from 0:9 to 7TeV. Predictions of several QCD-inspired models as implemented in pythia are compared to the data.
Keywords: Hadron-hadron scattering; Compact Muon Solenoid; Large Hadron Collider (LHC); CMS detectors; High energy physics